(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
This article discusses the complex fundamentals of organizing history teaching. The process of teaching the subject of history and the cognitive process have similar features, which gives grounds to assert that their methodological foundations also have similarities. The history teaching system is based on dialectics to achieve its goals.